2019
DOI: 10.7759/cureus.5307
|View full text |Cite
|
Sign up to set email alerts
|

Using Micro-learning on Mobile Applications to Increase Knowledge Retention and Work Performance: A Review of Literature

Abstract: Micro-learning is an educational teaching method used to train users on multiple platforms. This article will provide a brief introduction to the concepts of short-term and long-term memory, and explain how micro-learning can be used to increase retention in learners. Micro-lessons can aid in negating the Ebbinghaus forgetting curve and can use reintroduction to keep retention at significantly higher levels. This process also speeds up the learning process overall because students avoid the phenomenon of menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 21 publications
2
113
0
5
Order By: Relevance
“…As such, mobile learning as "the process of coming to know through conversations across multiple contexts amongst people and personal interactive technologies" [27] has been used to cover current needs. Also, new notions have been emerged, such as Micro-learning as an educational teaching method used to train users on multiple platforms [28]. Concurrently, smart phone display screen with various user graphical interfaces have been reported and patented [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…As such, mobile learning as "the process of coming to know through conversations across multiple contexts amongst people and personal interactive technologies" [27] has been used to cover current needs. Also, new notions have been emerged, such as Micro-learning as an educational teaching method used to train users on multiple platforms [28]. Concurrently, smart phone display screen with various user graphical interfaces have been reported and patented [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, with our current experience we argue that playful micro-learning tools like Redgrasp hypothetically reinforce the students' intrinsic motivation/curiosity and playfulness (dopaminergic system), social competence (serotoninergic and oxytocinergic system) and their state of flow -a concept discussed later in this article. Interestingly, such tools have already been linked with circumventing the sensation of mental exhaustion and facilitating the movement of learned material from short-term to long-term memory (Shail, 2019). Further inspiration could be found within existing playful childhood pedagogy, the gaming industry, social sciences and creative industries, etc.…”
Section: Potential Relevance For Higher Educationmentioning
confidence: 99%
“…With the need for lessons tailored to distance learners, and technological challenges such as poor internet bandwidth to be tackled, UMC opted for the microlearning approach based on small learning units (lessons) connected to specific learning objectives [ 6 ]. The microlearning format, with its focus on one or a few learning objectives per lesson, also facilitates ‘just-in-time’ training and repetition, a key aspect of effective learning, where specific lessons that are needed during work can be easily identified and revisited [ 7 ]. A recent literature review of microlearning in the health professions concluded that it has demonstrated a positive effect on retaining both knowledge and confidence among health professional learners [ 8 ].…”
Section: Introductionmentioning
confidence: 99%